PENINGKATAN PRESTASI BELAJAR AL KITĀBAH DENGAN MODEL ACCELERETED LEARNING MENGGUNAKAN PENDEKATAN SAVI PADA SISWA KELAS VIII A MTS NEGERI SLEMAN KOTA - Helmy Fauzi Awaliyah (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2016)
This study is a classroom action research. The purpose of this study was to determine whether learning with using Accelerated Learning model using SAVI approach (Somatic, Auditory, Visual, and Intellectual) can improve learning achievement of Al-Kitâbah of class VIII A students at MTs Negeri Sleman Kota. This research is a Classroom Action Research which is a reflection of learning activities in the form of an act that deliberately and simultaneously appear and occur in a class. This research consists of two cycles to 36 students. Each cycle consists of four stages: planning, acting, observing, and reflection. Data collection is done by using observation, interview, test and documentation. The results of this study indicate that learning by using Accelerated Learning model using SAVI approach can improve learning achievement of Al Kitâbah in class VIII A of MTs Negeri Sleman Kota which occurs in two cycles and is implemented in four types of learning, namely somatic, auditory, visual, and intellectual.